Agreement between four high-sensitivity cardiac troponin assays and non-invasive testing, clinical and quality of care outcomes based on the 2020 ESC guidelines: results from the ROMICAT II trial. (3rd October 2022) - Karady, J; Mayrhofer, T; Nagurney, J T; Udelson, J E; Fleg, J L; Peacock, W F; Januzzi, J L; Koenig, W; Ferencik, M; Hoffmann, U
Abstract: Background: Quality of care and safety of patients with suspected acute coronary syndrome (ACS) would greatly benefit if management was independent of which high-sensitivity cardiac troponin (hs-cTn) assay was used for risk stratification. Purpose: To assess the agreement of 4 hs-cTn assays to risk stratify patients with suspected ACS using the ESC2020 Guidelines 0/2-hour algorithm, and to assess their associations with non-invasive diagnostic testing, clinical- and quality of care outcomes. Methods: We analyzed blood samples obtained at emergency department (ED) presentation and 2 hours later from patients with suspected ACS enrolled in the ROMICAT (Rule Out Myocardial Infarction/Ischemia Using Computer Assisted Tomography) II trial, using 4 hs-cTn assays (Roche Diagnostics, Elecsys 2010; Abbott Diagnostics, ARCHITECT i2000SR; Siemens Diagnostics, HsVista; Beckman Coulter, ACCESS). We determined the agreement between the assays to assign patients to rule-out, observe, and rule-in management pathways according to the ESC2020 Guidelines. Further, we assessed assay association with non-invasive diagnostic test findings and adjudicated clinical- and quality of care outcomes. Finally, we compared observed conventional troponin management with predicted management per ESC2020 guidelines using hs-cTn assays. Results: Overall, assignment to ESC2020 Guideline management pathways among 238 patients with suspected ACS (age 52.7±8.0 years; 40.3% [96/238] female) was concordant across all hs-Tn assays in 74% of patients but differed for rule-out rates (89.9% vs 76.5% vs 78.6% vs 86.6%, p<0.001) and observation rates (6.7% vs 20.6% vs 17.7% vs 9.2%, p<0.001), but not for rule-in (3.4% vs 2.9% vs 3.8% vs 4.2%, p=0.623). Among those whose management recommendation was rule-out, 19.1–21.6% had obstructive CAD defined as coronary stenosis ≥50% on coronary CT angiography or inducible myocardial ischemia on perfusion imaging and 3.3–4.2% were diagnosed with ACS as adjudicated by independent panel. Predicted ED discharge rates based on hs-cTn assays were higher than those observed with conventional troponin (80.3% to 90.8% vs. 21.0%, respectively p<0.001). As a result, predicted costs of care were significantly lower based on strategies utilizing hs-cTn assays than with conventional troponin ($2, 578±2, 896 to $2, 894±4, 371 vs $3, 889±4, 833, respectively, p<0.001) Conclusion: In a quarter of patients presenting to the ED with suspected ACS ESC2020 Guideline-based management may be different, depending on the hs-cTn assay. As compared to conventional troponin, hs-cTn is predicted to significantly increase direct ED discharges and lower costs of care. Funding Acknowledgement: Type of funding sources: None.